Indirect assessment of sedimentation in hydropower dams using MODIS remote sensing images - Condé, Rita de Cássia; Martinez, Jean-Michel; Pessotto, Marco Aurélio [UNESP]; Villar, Raúl; Cochonneau, Gérard; Henry, Raoul [UNESP]; Lopes, Walszon; Nogueira, Marcos [UNESP] (MDPI, 2019)
In this study, we used moderate resolution imaging spectroradiometer (MODIS) satellite images to quantify the sedimentation processes in a cascade of six hydropower dams along a 700-km transect in the Paranapanema River in Brazil. Turbidity field measurement acquired over 10 years were used to calibrate a turbidity retrieval algorithm based on MODIS surface reflectance products. An independent field dataset was used to validate the remote sensing estimates showing fine accuracy (RMSE of 9.5 NTU, r = 0.75, N = 138). By processing 13 years of MODIS images since 2000, we showed that satellite data can provide robust turbidity monitoring over the entire transect and can identify extreme sediment discharge events occurring on daily to annual scales. We retrieved the decrease in the water turbidity as a function of distance within each reservoir that is related to sedimentation processes. The remote sensing-retrieved turbidity decrease within the reservoirs ranged from 2 to 62% making possible to infer the reservoir type and operation (storage versus run-of-river reservoirs). The reduction in turbidity assessed from space presented a good relationship with conventional sediment trapping efficiency calculations, demonstrating the potential use of this technology for monitoring the intensity of sedimentation processes within reservoirs and at large scale.
Keywords: MODIS; Paranapanema River; Remote sensing; Reservoir; River sediment discharge; Sediment trap efficiency; Sedimentation; Suspended particulate matter; Turbidity; Water color